Ferroelectric polymer nanocomposite alignment layer in twisted nematic liquid crystal devices for reducing switching voltage. Issue 5 (9th April 2019) - John V, Nimmy; Rajeev, Sreenidhi Prabha; Varghese, Soney
ABSTRACT: Twisted nematic liquid crystal device (TNLCD) was fabricated using a ferroelectric zinc oxide (ZnO)-doped polyimide alignment layer. The ferroelectric nanoparticle can produce a local electric field, which can trigger the orientation of liquid crystal molecule and reduces the switching voltage. The uniform dispersion of ferroelectric ZnO nanoparticles in the alignment layer was studied using field emission scanning electron microscopy and atomic force microscopy. The ferroelectric property of ZnO-doped polyimide was investigated using dynamic contact electrostatic force microscopy. An increased local electric field due to the presence of nano ZnO was confirmed with the help of scanning tunnelling microscopy. An augmentation of capacitance was observed with an increase in concentration, which substantiates the reduction of switching voltage of TNLCD with the modification of ferroelectric nanoparticle-doped alignment layer. GRAPHICAL ABSTRACT: